Second Life in Healthcare Education: Virtual Environment's Potential to Improve Patient Safety - Lee, Angie; Berge, Zane L. (My University, 2011)
Research has shown that a large portion of healthcare cost is due to medical errors. There are many factors that cause medical errors but one major factor is linked to healthcare professionals who are not adequately trained with the appropriate skills. Virtual environments and simulations are being used to help improve training in many different areas, including the healthcare profession. This paper explores the usage of Second Life in healthcare education and its ability to improve patient safety. The conclusion is that much progress and development still needs to be made before Second Life will make a significant impact on improved patient safety through healthcare education. There is a need to make the virtual environment more realistic to adequately train healthcare professionals.
Keywords: healthcare education; Second Life; Virtual environments; Patient safety; UMBC Instructional System Design